The role of the kidney in canine blood pressure control: direct assessment of the closed-loop gain - Persson, Pontus B.; Ehmke, Heimo; Kirchheim, Hartmut; Lempinen, Marko H.; Nafz, Benno (The journal of physiology, 1993)
1. The feedback control of arterial blood pressure by the kidney in the range of hours was investigated in resting, conscious foxhounds. 2. A servo-control device (connected to an aortic occlusive cuff implanted above both renal arteries) was used to maintain a constant pressure difference of 20 mmHg between aortic pressure measured proximal (mean arterial blood pressure: MAP) and distal (renal artery pressure: RAP) to the aortic cuff. 3. Protocol 1 (n = 6) served as a 4 h time control without intervention, protocol 2 (n = 6) consisted of three periods: after a control of 20 min duration, the servo-control device was activated for 180 min; this was followed by a recovery period of 40 min. Protocol 3 (n = 6) was as protocol 2, but during converting-enzyme inhibition. 4. Servo-control increased plasma renin activity (PRA) transiently from 0.5 ng angiotensin I (AI) ml-1 h-1 to a peak value of 2.4 ng AI ml-1 h-1, subsequently both RAP and MAP rose to reach a new steady state. During this increase in RAP, PRA declined to 1.4 ng AI ml-1 h-1. 5. On average, the compensation of the pressure decrease sensed by the kidney amounted to 63% of the error signal (closed-loop gain of 0.63 +/- 0.1). 6. Converting-enzyme inhibition reduced this closed-loop gain significantly (protocol 2 vs. protocol 3, 0.63 +/- 0.1 vs. 0.15 +/- 0.1; P < 0.05). 7. It is concluded, that the kidney plays an important role in medium-term blood pressure regulation, most probably via the renin-angiotensin system.